Theory of Synthesis of Asymmetrical Delay Line with the Surface Acoustic Wave - ŠIMKO, Milan; GUTTEN, Miroslav; CHUPÁČ, Milan; KUČERA, Matej; GLOWACZ, Adam; KANTOCH, Eliasz; LIU, Hui; BRUMERCIK, Frantisek (Archives of Acoustics, 2019)
The aim of this publication is to design a procedure for the synthesis of an IDT (interdigital transducer) with diluted electrodes. The paper deals with the surface acoustic waves (SAW) and the theory of synthesis of the asymmetrical delay line with the interdigital transducer with diluted electrodes. The authors developed a theory, design, and implementation of the proposed design. They also measured signals. The authors analysed acoustoelectronic components with SAW: PLF 13, PLR 40, delay line with PAV 44 PLO. The presented applications have a potential practical use.